PENGARUHDISIPLINKERJADAN MOTIVASI KERJATERHADAPKINERJAGURUDI SMANEGERI 1OBI - Irsan Labaraja; Karim Abubakar (Jurnal Manajemen Sinergi, 2015)
hisstudyaims todetermine theeffect of workdisciplineandmotivation toworkontheperformanceof teachers inSMANegeri 1Obi. Inpractice it is still very lowwhichhasbeenapplied is lesseffectiveandefficient way toachievea moreoptimal teacher performance that ithaskesesusaianwiththetaskofteachers aswell as ineducational andcultural kementerianhavethe recommended (RI Kepmendikbud:025/O/1995),This study uses a quantitative researchwhere data collection is done by distributingquestionnairesso as to digdeeper into theworkdiscipline of teachers and teachers' work motivation. The sample in this study was overall ateacherwho hasserved in SMANegeri 1Obi asmanyas39 teachers.The resultsobtained fromthisstudystatedworkdisciplineandmotivation towork in theSMANegeri 1Obi has implementedand applied. Results of the analysisshowed that thevariablesof workdiscipline(X1)hasaninfluence on the performanceof teachers(Y)equal to 4.911.Meanwhile,workmotivation(X2)hasan influenceon theperformanceof teachers(Y)of -2.664.Thus it canbesaid that the influenceof labor disciplineandmotivation toworkhasaweak relationship totheperformanceof teachersinSMANegeri 1 Obi.